Synthesis and characterization of Ce_(0.8)Sm_(0.2)O_(1.9) nanopowders using an acrylamide polymerization process - 郑颖平 王绍荣 王振荣 邬理伟 孙岳明 (Journal of rare earths, 2010)
Ce0.8Sm0.2O1.9(SDC) nanopowders were synthesized by an acrylamide polymerization process.The XRD results showed that SDC powders prepared at 700 °C possessed a cubic fluorite structure.Transmission electron microscopy(TEM) indicated that the particle sizes of powders were in the range of 10-15 nm.A 98.3% of theoretical density was obtained when the SDC pellets were sintered at 1350 °C for 5 h,indicating that the powders had good sinterability.The conductivity of the sintered SDC ceramics was 0.019 S/cm at 6...